UPAYA PENYELESAIAN HUKUM TERHADAP PINJAMAN BERMASALAH DI UNIT SIMPAN PINJAM KOPERASI SERBA USAHA SATYA DHARMA DENPASAR - Pramesthi Kusuma, Ida Ayu; Wiryawan, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2014)
The main income source of business cooperatives saving and loan units, in lending activities trhough a cooperative is usually the case the obstacles often faced such as lonas or borrowers are often unable to refund the amount of money borrowed. Resulting in channeling funds to members or cooperative customers become obstructed. Purpose of this paper is to determine the effort and law against non-performing loans in the saving and loans cooperative unit satya dharma. This study uses the type emperis lae. Emperis research is that reveals the law of life in society through action carried out by the community. This action doubles as a pattern that is applied and become the normative legal form and applicable law living in the community. Factor in causing the unit loan savings and loan business cooperatives is satya dharma can be seen from two factors internal and external, factors internal factors as the cause of the troubled loans in the form of weakness in the loan disbursement policy, whereas external factors as the cause of the troubled loans may be the occurrence of natural disasters and war. Efforts in the completion of the law against non-performing loans in the unit savings and loan business coopperatives satya dharma with debtors resolved by way of settlement of non-performing loans nonditigasi is to perform some action that is repressive and preventive measures.
Keywords: efforts completion, troubled loans, business cooperatives